Pulmonary agenesis and respiratory failure in childhood - Paula Vanessa Valverde Dinamarco; Cesar Cilento Ponce (University of São Paulo, 2015)
Pulmonary agenesis (PA) is a rare congenital anomaly, which may be unilateral or bilateral. Unilateral PA may be associated with nonspecific respiratory symptoms. We report the case of 5-month-old infant who presented a normal development until the age of 4 months when a respiratory infection caused an acute respiratory distress syndrome with a fatal outcome. The autopsy findings depicted the right lung agenesis without any other concomitant malformation. Although respiratory symptoms represent frequent complaints in pediatrics, the aim of this study is not only to draw attention to the unilateral pulmonary agenesis as a possible underlying malformation in children who present recurrent and severe respiratory symptoms, but also to report a case diagnosed at autopsy.